2019
DOI: 10.1016/j.heliyon.2019.e01293
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic and neuronal phenotype of NPC1−/− mice

Abstract: Niemann-Pick type C disease (NPC) is a fatal autosomal recessive disorder characterized by a defect in the intracellular transport of lipoproteins leading to the accumulation of lipids in diverse tissues. A visceral and neuronal phenotype mimicking human NPC1 disease has been described in NPC1 mutant mice. These mice are by now the most widely used NPC1 rodent model to study NPC and developmental compounds against this devastating disease. Here we characterized NPC1−/− mice for their hepatic and neuronal pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 63 publications
4
9
0
Order By: Relevance
“…We measured the activity of three liver enzymes, alkaline phosphatase (AP), alanine aminotransferase (ALT) and aspartate aminotransferase (AST), in the serum and showed significantly elevated levels in Npc1 mutant mice (Npc1 -/-/Pcsk9 -/-(n = 9) or Npc1 -/-/Pcsk9 +/+ (n = 6)), compared to the control groups (Npc1 +/+ /Pcsk9 +/+ (n = 4) or Npc1 +/+ /Pcsk9 -/-(n = 8)), which were within the normal range ( Figure 5). The elevated values in Npc1 -/mice are consistent with values published previously for Npc1 -/mice on a Balbc background [45]. Levels of ALT were reduced in the Npc1 -/-/Pcsk9 -/mice compared to Npc1 -/-/Pcsk9 +/+ (p = 0.031) ( Figure 5B), whereas AP and AST were not significantly different ( Figure 5A,C) suggesting that the diseased liver function in Npc1 -/-/Pcsk9 -/mice was equivalent to or even less than the Npc1 -/-/Pcsk9 +/+ mice at this age.…”
Section: Serum Liver Enzymes and Cholesterol Analysessupporting
confidence: 92%
See 1 more Smart Citation
“…We measured the activity of three liver enzymes, alkaline phosphatase (AP), alanine aminotransferase (ALT) and aspartate aminotransferase (AST), in the serum and showed significantly elevated levels in Npc1 mutant mice (Npc1 -/-/Pcsk9 -/-(n = 9) or Npc1 -/-/Pcsk9 +/+ (n = 6)), compared to the control groups (Npc1 +/+ /Pcsk9 +/+ (n = 4) or Npc1 +/+ /Pcsk9 -/-(n = 8)), which were within the normal range ( Figure 5). The elevated values in Npc1 -/mice are consistent with values published previously for Npc1 -/mice on a Balbc background [45]. Levels of ALT were reduced in the Npc1 -/-/Pcsk9 -/mice compared to Npc1 -/-/Pcsk9 +/+ (p = 0.031) ( Figure 5B), whereas AP and AST were not significantly different ( Figure 5A,C) suggesting that the diseased liver function in Npc1 -/-/Pcsk9 -/mice was equivalent to or even less than the Npc1 -/-/Pcsk9 +/+ mice at this age.…”
Section: Serum Liver Enzymes and Cholesterol Analysessupporting
confidence: 92%
“…No obvious differences were seen between the Pcsk9 +/+ and Pcsk9 +/mice and these data were combined as Pcsk9 ctrl . Single knockout Npc1 -/-/Pcsk9 ctrl male (n = 10) and female (n = 14) mice had an initial normal, but slightly reduced, weight-gain followed by weight loss starting at about 6-7 weeks of age as expected for the Npc1 -/phenotype [44,45]. In the double knockout Npc1 -/-/Pcsk9 -/mice, both male (n = 6) and female (n = 7) mice were similar to the Npc1 -/-/Pcsk9 ctrl mice, showing a similar weight loss pattern consistent with the phenotype of Npc1 -/mutant mice alone ( Figure 1A,B).…”
Section: Knockout Of Pcsk9 Did Not Significantly Alter Weight Progresmentioning
confidence: 71%
“…The astrogliosis observed in this study (Fig. 5 ), as well as microglial activation, begins in brain of the NPC1 −/− mouse as early as 2 weeks of age 33 , 34 . Suppression of myelin production begins as early as 5 weeks of age 35 .…”
Section: Discussionsupporting
confidence: 54%
“…Previous studies showed activation of glial cells in the CNS of NPC patients and animal models with distinct cell type-and region-specific onsets (Baudry et al, 2003;Cologna et al, 2014;Cougnoux et al, 2018;Cougnoux et al, 2020;Gabande-Rodriguez et al, 2019;German et al, 2002;Kavetsky et al, 2019;Lopez et al, 2011;Luan et al, 2008;Maue et al, 2012;Maulik et al, 2012;Park et al, 2019;Pressey et al, 2012;Repa et al, 2007;Santiago-Mujica et al, 2019;Seo et al, 2014;Stein et al, 2012;Tanaka et al, 1988;Walterfang et al, 2020;Yan et al, 2014a;Yan et al, 2014b). We asked how retinal glial cells react to the absence of NPC1 in 4-weeks-old mice.…”
Section: Reaction Of Retinal Glia To Npc1-deficiencymentioning
confidence: 99%